The Influence of Leadership Education on Organizational Culture: A Systematic Literature Review - I Kadek Laju; Samuel Dumak Parerungan (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
Leadership education is a strategic instrument in shaping the character, values, and behavioral orientation of individuals who act as driving forces in an organization. In the context of modern organizational dynamics, organizational culture is a key determinant of an institution's success in achieving its strategic goals. This article aims to systematically analyze the influence of leadership education on the formation and strengthening of organizational culture through a systematic literature review approach. This study uses a PRISMA-based literature selection protocol with the inclusion criteria of articles with international and national reputations from the past two decades. The results of the study indicate that leadership education has a significant effect on the internalization of organizational values, the formation of collective norms, increased member commitment, and consistency of work behavior. Transformational leadership, servant leadership, and authentic leadership models are the dominant approaches empirically proven to strengthen a collaborative, innovative, and ethically oriented culture. Systematically designed leadership education not only improves individual competency but also transforms the organizational value system in a sustainable manner. These findings emphasize the importance of integrating leadership curricula into organizational development strategies as a foundation for establishing an adaptive and competitive institutional culture.